Near-Field Thermal Transistor InSb/WSM/InSb (2023)
Near-field radiative heat transfer has attracted increasing attention in recent years in the development and manufacturing of thermal devices analogous to the building blocks of current microelectronics. In this work, we study theoretically a near-field thermal transistor operating at room temperature. The source and drain were assumed as indium antimonide (InSb) plates, whereas the gate as a Weyl semimetal (WSM). Numerical results computed using the fluctuational electrodynamics framework indicate that the modulation and/or amplification of the heat flux in the considered transistor can be achieved by modifying the gate temperature, and by the action of an external magnetic field upon the system. Results obtained in this work make the proposed near-field thermal transistor a suitable candidate for the contactless devices for the heat flux control and thermal management at nanoscale.